Test of Burn Wounds Healing Effects of Collagen From Snakehead Fish (Channa striata) Bone in The Preparation of Cream on Male White Rats (Rattus norvegicus) - Hasri, Najwa Miladi; Zebua, Nilsya; Sudewi (Indonesian Journal of Pharmaceutical and Clinical Research, 2020)
Abstract. The use of snakehead fish (Channa striata) collagen in cream is an alternative toreduce fish wastes. It has been proved that snakehead fish (Channa striata) contain collagen.This research aims to study the burn wound healing effectivity of bone’s collagen fromsnakehead fish (Channa striata) that is formulated into a cream. This study used theexperimental method with the bone of snakehead fish (Channa striata) as a sample. This studyconsisted of 4 (four) such as isolation of collagen from snakehead fish's (Channa striata) bone,characterization of collagen by analyzing moisture, ash, protein, fat and functional groupanalysis with FTIR, formulation, and evaluations of cream such as organoleptic test,homogeneity test, pH measurement, stability test, and irritation test, and burn wound healingtest in male white rats (Rattus norvegicus) and the result is analyzed using SPSS 22.0 Free trialand One Way ANOVA and Post-Hoc Tukey HSD. The results showed that fish collagen couldbe isolated from snakehead fish (Channa striata) and the yield obtained is 33.3%. The results ofcollagen characterization and evaluation test met the collagen standard requirements. Results ofthe burn wound healing test on male white rats (Rattus norvegicus) showed that K1 burn woundrecovered on day 21, K2 on day 12, K3 on day 15, K4 on day 18, and K5 on day 18.Measurement of burn wound diameter on day 21 showed K1 = 1.20 cm, K2 = 0.15 cm, K3 =0.10 cm, K4 = 0.45 cm, K5 = 0.40 cm. The results of the statistical analysis of burn wounddiameter showed a significant difference p = 0,000 (p <0.05) between each group. K3 showedthe reduction in the burn wound diameter is faster and the smallest, it can be concluded that theoptimal dose of snakehead fish bone’s collagen cream is a concentration of 3%.